Metals Process Simulation 2010
DOI: 10.31399/asm.hb.v22b.a0005505
|View full text |Cite
|
Sign up to set email alerts
|

Design Optimization Methodologies

Abstract: The process of optimization involves choosing the best solution from a pool of potential candidate solutions. This article provides a description of some classes of problems and the optimization methods that solve them. These problems include the deterministic single-objective problem, the deterministic multiobjective problem, and the nondeterministic, stochastic optimization problem. The article presents several complementary approaches to solve a wide variety of single-objective and multiobjective mechanical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Related experiments [33] have shown that the designed CAS airfoils, which developed by University of Chinese Academy of Sciences, have stable aerodynamic performance. In this work, the new aerodynamic modules for serrated airfoils are introduced in section 2.3 and an optimal design framework for serrated airfoils is developed using Isight software [34]. The framework handles a set of design variables related to the parameterization of the serrated airfoil shape and solves the aerodynamic efficiency problem by taking into account the stringent aerodynamic and structural performance constraints defined in section 2.2, as schematically shown in figure 4.…”
Section: Integrated Optimization System 241 Design Strategymentioning
confidence: 99%
“…Related experiments [33] have shown that the designed CAS airfoils, which developed by University of Chinese Academy of Sciences, have stable aerodynamic performance. In this work, the new aerodynamic modules for serrated airfoils are introduced in section 2.3 and an optimal design framework for serrated airfoils is developed using Isight software [34]. The framework handles a set of design variables related to the parameterization of the serrated airfoil shape and solves the aerodynamic efficiency problem by taking into account the stringent aerodynamic and structural performance constraints defined in section 2.2, as schematically shown in figure 4.…”
Section: Integrated Optimization System 241 Design Strategymentioning
confidence: 99%
“…The CMDO framework is implemented as a workflow in Isight [4]. Isight is a process-integration, design-optimization software developed and distributed by Dassault Systemes.…”
Section: A Conceptual Multi-disciplinary Optimization Frameworkmentioning
confidence: 99%
“…In this section, we introduce six optimizers to solve the following constrained problem: Volume availability factor B[0] g [3] Landing gear spacing B[3] g [1] C L ma x retracted B [1] g [4] Wingtip twist deformation B[4] g [2] Cruise deck angle B [2] where f : R d → R is the objective function, g : R d → R m gives the inequality constraints which are expensive to evaluate and x ∈ Ω ⊂ R d is the vector of design variables. Two of the optimizers are included in the Isight software, which is mandatory to use because of CMDO and PMDO frameworks.…”
Section: Optimizersmentioning
confidence: 99%
See 2 more Smart Citations